Comparative study on histological structure of gill of Silver Sharkminnow fish (Osteochilus hasselti C.V)from the Tarai and Sibam Rivers Riau Province - Hutajulu, Magdalena Dwiyani; Efizon, Deni; Putra, Ridwan Manda (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT             Osteochillus hasselti is present in the Tarai River that has relatively good water quality, as well as in the Sibam River that has polluted water. The water condition of the rivers my affects the fish health status in general. A study aimed to understand the histological structure of gill of the fish from those rivershas been conducted from February to April 2018. Fish organs were histologically processed and stained (HE). Results shown that in general, the histological structure of the gill of fish from both areas shown abnormality. Cell abnormality such as hyperplasia, oedema, hypertrophy, curling of the secondary lamella, and telangiectasis are present in all fish. The Histopathological Alteration Index (HAI) values, however shown that the  Tarai fish gill was better than that of the Sibam fish, they were 1.44 and 23.77 respectively.Keywords:gill condition, fish organ, Histopathological Alteration Index , gill abnormality